Student Voice : Reviewing two decades of the literature to guide the next 20 years. - Ashton-Hay, Sally (Journal of University Teaching & Learning Practice v.22 n.1 p.1-18 https://doi.org/10.53761/w9tde483, 2025)
Attention to students and their education experiences has become increasingly important in the 21st century. Student experience - particularly active and agentic practices captures in terms like 'student voice' and 'partnership' - was an obvious choice in response to Journal of University Teaching and Learning Practice (JUTLP) editors' commissioned series of literature reviews analysing 20 years of the journal's publications. A hybrid method for the systematic review was guided by the question: What has been published about student voice and partnership in JUTLP, and how has this scholarship evolved over the journal's 20-year history? A student voice and partnership framework adapted from Fielding (2004, 2012) was developed to provide theoretical guidance for the review. In total, 92 publications were identified and described quantitatively (year, country, research design, etc) and qualitatively using reflexive thematic analysis. Overall, the findings show increased publications over time that document active student involvement in developing, shaping ,designing, evaluating or researching alongside staff. The upward trend of partnership is a marked change from early JUTLP publications that studied students as objects of research and sources of data with passive roles in education practices and student life activities. The trend is toward students as active, agentic participants, partners and leaders in shaping and influencing their education experiences. Moving into the next 20 years, the JUTLP community is urged to engage with students as co-authors, co-researchers, and co-designers to report on educational praxis with staff and to open up new avenues for student contributions to knowledge and the mission of JUTLP. [Author abstract]